The role of caregiver gestures and gesture-related responses of toddlers with autism spectrum disorder - Lv, ShaoLi; Xing, Yu; Xu, YanTing; Liu, LinRu; Zhu, HuiLin; Ye, QianYing; Wang, ChunMei; Zou, XiaoBing; Deng, HongZhu (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is characterized by social communicative abnormalities. Deficits and delays in gestural communication are among the early deficits of ASD and also a major social modality in early caregiver-toddler interaction. Caregiver gestures have an important role in the cognitive and social development of children with ASD. Thus, it is urgent to further explore the role of caregiver gestures in early caregiver-toddler interaction. In this cross-sectional study, we observed the caregivers’ gestures and responses of toddlers aged between 18 and 24 months during play (ASD = 44, TD = 29) and dining activities (ASD = 34, TD = 27). By observing the different frequencies and patterns of gestures by the caregiver-child interaction and the different proportions of children's responses to the caregiver's gestures, we found that, compared to caregivers of typically developing toddlers, caregivers of toddlers with ASD had fewer synchronized gestures and more unsynchronized gestures in the play activity and more supplementary gestures in dining activity. Toddlers with ASD produced more social responses to caregivers’ synchronized gestures, whereas the use of synchronized gestures by the caregivers in caregiver-toddler interaction had a positive influence on social responses to toddlers with ASD. The findings suggest that effective use of gestures by caregivers during caregiver-toddler activities can improve children’s social responses.